SCHIZOSTACHYUM LUMAMPAO (BYUYU): ITS DIVERSE ETHNO-BOTANICAL USES BY LUBUAGAN SUB TRIBE OF KALINGA IN NORTH LUZON PHILIPPINES - T.P. Banwa; M.C.C. Bawer (European Scientific Journal, ESJ, 2014)
Bamboos are widely used by indigenous people in the tropical regions for different purposes. Schizostachyum lumampao is one of the bamboo species utilized by different ethnic groups in the Philippines. This study determined how the Lubuagan sub-tribe of Kalinga of the Cordillera Region Northern Philippines used Schizostachyum lumampao in their daily life. Selected key informants from the different communities of Lubuagan municipality were interviewed about the ethno-botanical uses of this species. These uses were verified through field observations and photo-documentations. Schizostachyum lumampao was found to be an integral part of the Lubuagan sub-tribe life. This bamboo species is a versatile source of materials for surgical tools, agricultural implements, shelter constructions, socio-cultural activities and indigenous musical instruments. These integral ethnobotanical uses of S. lumampao show the importance of bamboo plants to indigenous people`s life that need to be conserved.